Clinicopathological and Prognostic Significance of PRMT5 in Cancers: A System Review and Meta-Analysis. (1st October 2021) - Liang, Zhenzhen; Liu, Lianchang; Wen, Chaowei; Jiang, Heya; Ye, Tianxia; Ma, Shumei; Liu, Xiaodong
Purpose: Since protein arginine methyltransferase 5 (PRMT5) is abnormally expressed in various tumors, in this study we aim to assess the association between PRMT5 and clinicopathological and prognostic features. Methods: Electronic databases including PubMed, Web of Science, Scopus, ScienceDirect, and the Cochrane Library were searched until July 25, 2021. The critical appraisal of the eligible studies was performed using the Newcastle–Ottawa Quality Assessment Scale. Pooled hazard ratios (HR) and pooled odds ratios (OR) were calculated to assess the effect. Engauge Digitizer version 12.1, STATA version 15.1, and R version 4.0.5 were used to obtain and analysis the data. Results: A total of 32 original studies covering 15, 583 patients were included. In our data, it indicated that high level of PRMT5 was significantly correlated with advanced tumor stage (OR = 2.12, 95% CI: 1.22-3.70, P =.008; I 2 = 80.7%) and positively correlated with poor overall survival (HR = 1.59, 95% CI: 1.46-1.73, P < .001; I 2 = 50%) and progression-free survival (HR = 1.53, 95% CI: 1.24-1.88, P < .001; I 2 = 0%). In addition, sub-group analysis showed that high level of PRMT5 was associated with poor overall survival for such 5 kinds of cancers as hepatocellular carcinoma, pancreatic cancer, breast cancer, gastric cancer, and lung cancer. Conclusion: For the first time we found PRMT5 was pan-cancerous as a prognostic biomarker and high level of PRMT5 was associated with poor prognosis for certain cancers.